A new species of Enterognathus (Copepoda, Cyclopoida, Enterognathidae) collected from the Seto Inland Sea, western Japan - Ohtsuka, Susumu (Pensoft Publishers, 2012)

(untitled)
Abstract. A new species of the endoparasitic copepod Enterognathus (Cyclopoida, Enterognathidae) is described from a crinoid host in the Seto Inland Sea, western Japan. This is a third species of the genus and its first occurrence in the Pacific Ocean. The new species is distinguished from two previously known congeners by the morphology of the body somites, caudal rami, antennae and legs. Crinoid parasites belonging to Enterognathus and the closely related genus Parenterognathus have a broad distribution from the northeastern Atlantic through the Red Sea to the West Pacific.